Blue's clues & you!. Rainbow puppy adventures [videorecording (DVD)]. - Dela Cruz, Joshua, 1989- (Paramount, 2022)
"Meet Rainbow Puppy - a confident puppy from the big city who can turn any day into a musical adventure! Rainbow Puppy has a flair for drama and fun, exudes passion and positivity, and breaks into song ALL. THE. TIME. And like Blue, she can mark clues with her own special, sparkly rainbow paw print! Come along on spectacular adventures with Josh, Blue, Periwinkle, and Rainbow Puppy!" --Container.